Impact of Cooking Methods on Physicochemical and Sensory Attributes of Apple Gourd - Aamna Soomro,; Asadullah Marri,; Nida Shaikh,; Aijaz Hussain Soomro,; Shahzor Gul Khaskheli, (Journal of Basic & Applied Sciences, 2018)
An investigation was carried out to examine the influence of some cooking methods on physicochemical and sensory characteristics of apple gourd during 2016-17. For this purpose, vegetable was procured, washed, peeled, sliced and distributed in five equal lots. Four of these lots were used for individual cooking treatments (i.e. T2=boiling, T3=steaming, T4=frying and T5=microwaving), however, last lot was treated as control (i.e. T1=raw/without treatment). After cooking, all samples were used for analysis. It was found that all organic acids (%) i.e. acetic acid, citric acid, oxalic acid and tartaric acid remained significantly higher (P<0.05) in T4, average pH value and moisture content (%) in T2, however, ash, dry matter, fiber content (%) and total soluble solids (Brix°) in T4. Present study also revealed that T4 perceived significantly higher (P<0.05) score for all sensory attributes i.e. color, aroma, taste texture and overall acceptability. It can be concluded from the present study that all cooking treatments applied on apple gourd showed variable impact upon overall physicochemical and sensory properties. It can also be concluded that T4 treatment remained most suitable for maintaining the quality attributes of apple gourd followed by T5, T3, T2 and T1.